EFEKTIVITAS MEDIA CODING DALAM MENINGKATKAN MOTIVASI BELAJAR ANAK USIA DINI USIA 5-6 TAHUN - Novita Sari; Endah Wahyu Sugiharti (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study aimed to examine the effectiveness of coding learning media (coding worksheets) in improving the learning motivation of early childhood aged 5-6 years. The research used a qualitative approach with a case study design conducted at TK Pertiwi Pacitan. The research subjects were 5 children aged 5-6 years. Data were collected through observation, structured interviews, and documentation. The results showed that the use of coding worksheets as learning media significantly increased children's learning motivation. The average learning motivation score increased from 35% (session 1) to 87% (session 8). Individual scores showed Aisyah improved from 32% to 88%, Shankara from 38% to 90%, Humeera from 30% to 85%, Zidan from 40% to 86%, and Qinara from 35% to 87%. Indicators of improved motivation included active engagement in activities, enthusiasm, curiosity, and persistence in completing tasks. This study concludes that coding media is effective and relevant as an innovative learning medium for early childhood education.